Redox phenotype confers T cell-exclusion microenvironment and resistance to immunotherapy by suppressing STING/MDA5 expression and interferon signaling in lung cancers harboring KEAP1/STK11 mutations - Shrestha, Ashish; Li, Yangchan; Huang, Lixia; Li, Shaoli; Zhou, Yanbin; Gu, Jincui; Lin, Ziying (Frontiers in Oncology, 2025)
BackgroundKEAP1 and STK11 are frequently mutated in NSCLC, and are associated with compromised response to immunotherapy, the underlying mechanism of which is not fully understood.MethodsTo assess the impact of KEAP1/STK11 mutations on immune profiles, we analyzed RNA-seq data from the TCGA lung cancer cohort and the GSE72094 cohort. Differential expression, pathway enrichment, and correlation analyses were performed to elucidate the underlying mechanisms. Key findings were further validated using a single-cell RNA-seq dataset. Additionally, the prognostic significance of these mutations in immunotherapy was evaluated using immune checkpoint inhibitor (ICI) cohorts from our medical center and published studies.ResultsWe observed the simultaneous upregulation of pathways involved in oxidoreductase activity and down-regulation of interferon signaling pathways by mutation of KEAP1 or STK11, and developed a redox signature driven by KEAP1/STK11 mutations. Redox score exhibited negative correlation with expression of STING/MDA5, which function as sensors of dsDNA/dsRNA and activate downstream interferon signaling. Redox score and STING/MDA5 expression manifested the exact opposite impact on the infiltrating level of most immune cells. Analysis of single cell RNA sequencing dataset indicated that redox phenotype specifically impacted expressional level of STING/MDA5 in cancer cells but other cell types within tumor immune microenvironment. Prognostic significance of redox signature was validated in immunotherapy cohorts of lung cancer and melanoma, which all indicated a significant worse outcome associated with higher redox score.ConclusionsCollectively, we associated the redox status mediated by loss-function mutations of KEAP1 or STK11 to immune evasion and immunotherapeutic resistance by suppressing STING/MDA5 expression and interferon signaling of cancer cells. Our findings link redox homeostasis to STING/MDA5 expression and tumor immunogenicity, raising the possibility that targeting this axis could represent a future strategy to enhance ICI efficacy.